An Investigation of the Anti-Depressive Properties of Phenylpropanoids and Flavonoids in Hemerocallis citrina Baroni - Tiancheng Ma; Yu Sun; Lida Wang; Jinyu Wang; Bo Wu; Tingxu Yan; Ying Jia (Molecules, 2022)
The World Health Organization predicts that over the next several years, depression will become the most important mental health issue globally. Growing evidence shows that the flower buds of Hemerocallis citrina Baroni (H. citrina) possess antidepressant properties. In the search for new anti-depression drugs, a total of 15 phenylpropanoids and 22 flavonoids were isolated and identified based on spectral data (1D and 2D NMR, HR-ESI-MS, UV) from H. citrina. Among them, compound 8 was a novel compound, while compounds 1–4, 6, 9, 10, 15, 17, 24–26, 28, and 37 were isolated for the first time from Hemerocallis genus. To study the antidepressant activity of phenylpropanoids and flavonoids fractions from H. citrina, macroporous resin was used to enrich them under the guidance of UV characteristics. UHPLC-MS/MS was applied to identify the constituents of the enriched fractions. According to behavioral tests and biochemical analyses, it showed that phenylpropanoid and flavonoid fractions from H. citrina can improve the depressive-like mental state of chronic unpredictable mild stress (CUMS) rats. This might be accomplished by controlling the amounts of the inflammatory proteins IL-6, IL-1β, and TNF-α in the hippocampus as well as corticosterone in the serum. Thus, the monomer compounds were tested for their anti-neuroinflammatory activity and their structure–activity relationship was discussed in further detail.